A new optical switching network architecture with crosstalk free and nonblocking routing algorithm - Ahmed, Manjur; Rahman, Mostafijur; Che Rosli, Ahmad Nasir; Rahman, M.M. Hafizur; Malek, Fareq; Hossen, Md.Sakoat; Ahmad, R. B. (2010)
A new multistage interconnection network have been proposed with a suitable and straight forward routing algorithm that can realize input to output in a single pass and crosstalk free for any permutation. The switch network is wide sense nonblocking characteristics. The proposed network can be extended for large N×N network. We have also focused the appropriate routing algorithm of the proposed network. A graphical representation/simulation has been given for analyzing nonblocking and crosstalk free characteristics with single pass of the proposed network.